The Growing Role of Re-export in International Trade - V. N. Kirillov; Y. A. Savinov; A. E. Gudzenko (Vestnik MGIMO-Universiteta)
The article aims to determine the essence, role, and significance of re-export in international trade using its opportunities to develop Russian exports and imports.The authors define re-export and its key characteristics, analyze the main factors of re-export trade development, study re-export dynamics compared to the commodity supplies dynamics within the framework of ordinary exports. When exporting highly differentiated goods, it is the role of knowledge about the terms, forms, and trading methods on the international market that increases. Specialized trading companies possess this knowledge; they create large transport and logistics centers in the countries crossing international trade routes, including extensive consignment warehouses.The article studies the dynamics of re-export flows and makes calculations, based on which it concludes that the volume of these commercial operations is growing faster in the world market. At the same time, large re-export operations are now performed not only by small states located at the intersection of sea roads but also by large, industrialized states: the USA, Great Britain, Italy, etc.The authors conclude that an essential factor in the development of re-export was the growth of trade restrictions imposed primarily for political reasons. Such restrictions apply in trade relations between India and Pakistan, Israel and the Arab countries, between some states of the Persian Gulf, etc. The anti-Russian sanctions adopted in the United States and other Western states inadvertently contribute to the development of re-exports, since many trading companies, including Western ones conducting international commercial operations, do not consider themselves bound by unilateral decisions of the anti-Russian part of the US government. Many US trading companies themselves are actively involved in re-export operations without disclosing partners. Given the undesirability of disseminating information on re-export operations, many countries actively involved in re-export have stopped submitting data on their re-exports to international statistical agencies.The authors concentrate on the re-export operation of the United Arab Emirates, where are thousands of trading firms with transport and logistics infrastructure and consignment warehouses. Russia is involved in re-export trade, mainly through the UAE companies, carrying on export and import operations on the world market. The authors conclude that expanding the practice of re-export increases sales of national products in the world market.